Comparison of Silver, Zinc Oxide, and Chitosan-mediated Nanoparticle synthesis and their antifungal activity against Oral Candidiasis - NS, Shree Abiraami; Pillai, Devika; Rajeshkumar, S (International Journal of Membrane Science and Technology, 2023)
Aim: To analyze the effectiveness of silver, zinc oxide, and chitosan nanoparticles against oral candidiasis. Materials and Methods: Agar-well diffusion method: After the synthesis of AgNP, ZnONP, and ChNP In the agar plate, wells are cut, and 25 l, 50 l, and 100 l concentrations of the solution are placed. Reading was taken after 24 hours. The zone of inhibition was noted. Time-kill curve assay: RBA broth was prepared and sterilized, and 6 mL was added to all five test tubes. Candidia suspension was added to all five test tubes in the range of 5×105 CFU/ml. The first three tubes contain silver NP, zinc-oxide Np, and chitosan Np with three different concentrations; the fourth tube is considered the growth control, and the fifth tube is the standard (fluconazole). The incubation is done under suitable conditions for varied time intervals (1h, 2h, 3h, 4h, 5h). Then the percentage of dead cells is calculated at a wavelength of 540nm at regular time intervals. Results and Conclusion: From the agar well diffusion method, Ag Np showed 13mm , zinc-oxide Np 16 mm, and chitosan Np 17 mm zones of inhibition. From the time-kill assay, Chitosan Np at 50 µg/ml showed better bactericidal activity. Chitosan nanoparticles hold great potential as a novel approach for the management of candidiasis, offering improved drug delivery, enhanced antifungal activity, and the possibility of overcoming drug resistance.